Assessment and Feedback Practices in the English Language Classroom - Rahman, Md Fazlur; Babu, Rasel; Ashrafuzzaman, Md (Journal of NELTA, 2012)
The study mainly focused on exploring the nature of English language classroom assessment and feedback practised within Junior Secondary schools of Bangladesh. A qualitative approach was used to collect data by using classroom observation checklists, English teachers' and head teachers' interview schedules and Focus Group Discussions (FGDs) with students. Thematic analysis was conducted to pull out the findings of the study which showed that teachers assessed the students learning through questioning and the questions were closed-ended by nature. Most of the students liked written assessments. Students had contradictory opinions about liking speaking skills. In the classroom, teachers provided only verbal feedback to the students and in the observation it was found that teachers gave feedback on few occasions. Teachers recommended that listening and speaking test items be included within the national assessment system. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6133 NELTA 2011; 16(1-2): 97-106